Diseño de un Sistema Integrado de Tratamiento de las Aguas Residuales para Mitigar la Contaminación del Río Mayo, Sector Juan Antonio – Moyobamba, 2014 - del Aguila Valles, Violeta (2014)
The present research work entitled "Design a wastewater treatment system to mitigate the pollution of the river May, Juan Antonio Sector - Moyobamba, 2014" was developed in the Juan Antonio sector, area where is poured domestic wastewater produced in the Moyobamba city. It 's main object study to design a system for treating wastewater discharges into the river Mayo, Juan Antonio sector ; which it was conducted through the characterization of wastewater discharged to the Mayo River in order to propose a treatment system quantitatively evaluating the efficiency treatment levels. For such action was necessary to take samples, for then to be analyzed and to know the values of the parameters to treat. The same that allowed us to contrasting with the maximum permissible limits laid down in the national standard in force. The current state of the discharge of wastewater discharged into the river Mayo, Juan Antonio sector, getting a concentration of DBO5 472 mg DBO/L and thermotolerant coliforms 17333333.33 NMP/100ml exceeding the maximum permissible limits. Using the theoretical calculation used in this research was conducted for the dimensioning of bars camera, sand remover, primary lagoons optional and secondary lagoons optional, with which ensures the dumping of waste water according to the Peruvian normativity. Levels of system efficiency for wastewater treatment effluent to the river Mayo, Juan Antonio sector was assessed quantitatively , DBO5 472 mg / l passing the maximum permissible limits , performing the theoretical calculation according to the National Building Regulations that indicates calculate 50gDBO / hab obtain a removal of 98.14 % (9.68 mg / l). The thermotolerant coliforms with 17333333.33 NMP/100ml, which also exceeds the maximum permissible limits was reduced to 509 NMP/100ml. Finally, the final report of the investigation with theoretical calculations of each treatment was developed. Where the removal efficiency of the parameters indicated to treat.